Linguistic Intelligence: Improving Writing Ability through Mind Mapping of Project Based Learning - Widiastuti, Ni Putu Kusuma; Putrayasa, Ida Bagus; Pujawan, I Gusti Ngurah; Widiana, I Wayan (International Journal of Language Education, 2024)
The survey results show that students have low writing skills. One of the contributing factors is that students have difficulty developing ideas from writing, which causes the writing process to be slow. Apart from that, passive learning activities also have an impact on students' writing abilities. Based on this, the aim of this research is to analyze the influence of the Mind Mapping-based Project Based Learning (PjBL) Model on students' writing abilities. This type of research is quasi-experimental research (quasi-experimental) using a 2 x 2 factorial design. The population in this research is grade IV elementary school students, totaling 9 schools. The total sample size was 160 students. The sampling technique uses a simple random sample. The data collection method in research uses test and non-test methods. The technique used to analyze data is inferential statistics. The results of the research are that the writing ability of the group of students who were given the Mind Mapping -based Project Based Learning Model was greater than the group of students with low linguistic intelligence, the writing ability of the group of students who were given the Conventional Learning Model, after controlling for language knowledge. It was concluded that the Project Based Learning (PjBL) Model based on Mind Mapping can improve students' writing skills. The implication of this research is that the application of the Project Based Learning (PjBL) Model based on Mind Mapping can stimulate students' learning and stimulate students' thinking skills so that it has an impact on improving students' writing skills.